Heritage-based design - Meurs, Paul (Stichting Rondeltappe-Bernoster-Kemmers, 2024)
This book addresses the question of how to design in a historical context. How to get a grip on a site? How can a designer incorporate actual qualities of the heritage in the design? In three chapters, it is described how the conservation of heritage has increasingly become an issue of planning and intervention, with the specific cultural heritage qualities of a site as the starting point for transformation. There are several different approaches to embed the design in the site: focussing on the designed past, the designed presence and the non-designed presence. The better the essences of the meaning of the cultural heritage (substance, structure and narrative) are exposed, the better the design can focus on these. However accurately the different process steps are adhered to — in the end the quality of the design will determine the degree of success: it’s a thin line between a disaster and a brilliant intervention. The design challenge is to give a site new vitality while at the same time preserving its value. Over the past decade, my office has dealt with all kinds of interventions and new developments. In teams of designers and historians, we have analysed buildings, areas and landscapes to discover their visible and invisible qualities. How did they become what they are today? What were the ideas and ideals at the time of their realisation? To what extent has a site withstood the test of time, and how can the concepts, structures and stories from the past be deployed in current challenges? We gradually try to get to the core: the legacy for the future and the exact nature of the assignment — viewed from the perspective of the cultural heritage value. Defining that value is a design on its own, just like history itself is. It is a creative process, in which the views and opinions of others carry considerable weight, but where you as the specialist will have to make the final assessment to arrive at decisions and legitimation. This will create a heritage base for the design to respond to and build upon. This book is part of a series of books produced in cooperation with and financed by the Stichting Rondeltappe-Bernoster-Kemmers. All books of the series have been reviewed and edited by Silvia Naldini, Section of Heritage & Architecture, Faculty of Architecture and the Built Environment, Delft University of Technology, The Netherlands.